Pemanfaatan Instagram Sebagai Platform Mengunggah Text Types - Inayatul Ulya (JURNAL LITBANG KOTA PEKALONGAN, 2022)
The development of technology supports all of activities included teaching learning process. One of the component in the teaching learning process is evaluation. In conducting evaluation, there were some ways, one of them was doing a project. Since nowadays students spend more time on social media, Instagram was considered as an appropriate platform to post students’ work. The objectives of this study were to describe the use of Instagram as platform to post students writing project and to know the strength and weaknesses of it. Descriptive qualitative method was used to conduct this research. The second semester students of English department were the subject of this study. Meanwhile, the instruments were documentation and questionnaire. The result showed that the second semester students used Instagram to post their project in writing text types. Those works included writing narrative, recount, descriptive, report, explanation, procedure, news item, hortatory exposition, analytical exposition, and discussion text. However, there were strength and weaknesses. The strengths were that their work were easy to be accessed, their writing skill were developed, they became more creative and innovative, and they used the Instagram wisely. Meanwhile, the weaknesses were that there was length limitation for writing the caption on Instagram, and it needed long time to design the content, therefore it spent more internet kuota.   Keywords: Writing, text types, Instagram.